The Relationship Between Barriers and Drivers of COVID-19 Protective Behaviors in Germany and the UK - Farnaz Mahdavian; George W. Warren; Darrick Evensen; Frederic E. Bouder (Frontiers Media S.A., 2022)
Objectives: To explore and evaluate the impact of factors including public risk perceptions on COVID-19 protective behaviors across the UK and Germany.Methods: We used survey data collected from a representative sample for Germany and the UK (total N = 1,663) between April and May 2021. Using a Structural Equation Model, we evaluate the role of personal health risk perceptions, official message quality, source of news, age and political orientation on COVID-19 protective behaviors in the context of German and UK risk communication strategies.Results: Personal health risk perceptions had a significant positive influence on protective behaviors. Economic risk perceptions had a negative direct influence on protective behaviors, particularly in Germany, as well as a positive indirect influence. Official message quality, use of official news sources and age had positive impacts on risk perceptions and protective behaviors. Left-wing political orientation was linked to greater likelihood of undertaking protective behaviors.Conclusion: For future pandemics, more attention should be paid to evaluating and conceptualizing different varieties of risk perceptions, risk communication strategies, and demographic variables alongside their impacts on undertaking protective behaviors.